Types of Abortion and Its Consequences in Dhaka Medical College Hospital - Khatun, Rokhshana; Gani, Osman; Ghosh, Lipika; Manjari, Mamata (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: Among the gynaecological cases admitted in tertiary care hospitals, abortion occupies the highest position. But detailed studies about the pattern of abortion admitted in the hospitals are limited. The present study was intended to find the proportion of abortion cases to total admitted cases and describe the types, clinical presentation and consequences of abortions. Methods: This study was carried out among a cross-section of abortion patients admitted in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital. A total of 100 women admitted with a history of abortion between January and June, 2003 were consecutively included in the study. On admission, blood sample was sent for blood grouping & cross-matching and estimation of haemoglobin. Additional investigations like routine blood test, TC, DC, urine for R/E were done in septic abortion cases. High vaginal swab was collected from all cases but only in 5 patients, it was possible to carry out culture and sensitivity test. All cases were admitted and followed up to discharge for studying their consequences. Result: Majority (61%) of the patients was admitted in their third decade of life. The included cases were predominantly poor (68%), Muslim (97%) and urban residents (78%). Over half (54%) of the patients were illiterate. Sixty percent patients were multipara, 21% primipara and 19% nullipara. Two patients were unmarried. One-quarter had previous history of 1-4 abortions. Of the 100 cases of abortions, over three-quarters (77%) were of spontaneous abortions and 23% were of induced abortions. Two-thirds (66%) of the cases presented with incomplete abortions, which among others, included incomplete MR (13%). Septic abortion was 12%; of which 10% were induced and 2% spontaneous abortions, complicated to septic abortions. Missed abortion was 10%, inevitable 10% and threatened 6%. Out of 100 cases, 86% required operative intervention which included dilatation, evacuation and curettage (95.2%), subtotal hysterectomy, repair of perforation, hysterotomy and colpotomy. Two threatened abortions cases continued their pregnancy. One threatened abortion, five missed abortion, one septic abortion and six inevitable abortion cases spontaneously expelled their product of conceptus. Seventy-nine patients received whole blood transfusion to compensate for haemorrhage. Over 80% were discharged from the hospital within 5 days. Complications (except anaemia) of abortion were found in 49% cases. One case of septic abortion with endotoxic shock and severe anemia died of the disease. Conclusion: Complications of abortion are preventable if the patients are made aware about the grave consequences of abortion and appropriate health services are extended at field levels. Ibrahim Card Med J 2020; 10 (1&2): 66-73